O processo penal como instrumento de política criminal: uma análise crítica da discricionariedade regrada do Ministério Público - Goldfinger, Fábio Ianni (2022)
The criminal procedure as an instrument of criminal policy: a critical analysis of the public prosecutor's discretion is the theme chosen for the development of this work. The proposal is justified in view of the need to modify the criminal procedure, due to the current society - complex and disoriented - resulting from the parameters of modernization that impact criminal law and criminal procedure by bringing them several problems. Among them, mention should be made of the increase in the volume of criminal rules, the constant edition of symbolic criminal laws, the feeling of insecurity, widely disseminated by the media that "dictates the rules of criminal procedure", the congestion of processes and the lack of reasonableness. regarding the duration of the judicial process. he objective of this work is to analyze the criminal procedural system, its historical development and framing against the Federal Constitution. And, through this analysis, establish the role and function of the Public Ministry in the constitutional procedural system. Is the Public Ministry an inducer of criminal policy? Is it possible for the Public Ministry to exercise discretion in criminal proceedings? Are there limits to this discretion? The research methodology used is a literature review, based on national and international doctrine, as well as jurisprudential research. The study is essentially divided into four parts. The first one deals with the Brazilian criminal procedure: its history, the current criminal procedure, proposed changes and the constitutional influence. The second, the relationship of the criminal procedure as an instrument of criminal policy. The third emphasizes the models of criminal procedural systems and their impact on public criminal action and evidence management. The fourth is dedicated to addressing the discretionary role of the Public Ministry in the conduct of criminal prosecution when dealing with issues such as just cause for criminal action, the regime for closing criminal investigations and consensual criminal justice. It also addresses the need to establish legal certainty in the face of ministerial action, considering that the constitutional principle of functional independence must be based on uniform action (unity), in the search for balance and legal certainty, with the purpose of stabilizing social relations. The possibility is envisaged for the Public Ministry to act in concert with the concrete social reality, in a discretionary way in criminal prosecution, as an inducer of criminal policy